Features Of Teaching English to Multilevel Classes (Eurasian Journal of Learning and Academic Teaching, 2022)
This article is about teaching English to multilevel classes, and gives information about challenges, benefits, opinions how to conduct multilevel classes.A multi-level classroom is one in which some pupils are conversant with the Roman alphabet and others are not. Finally, the phrase multi-level can apply to a group of students who work together and have a wide range of abilities.